Pengaruh Kompensasi Dan Penempatan Kerja Terhadap Kinerja Pada Perawat Non Pns Di Rsud Dr. Dradjat Prawiranegara Dengan Kepuasan Kerja Sebagai Variabel Intervening - Susanti, Mutia Andini; Prahiawan, Wawan; Ramdansyah, Agus David (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2022)
The purpose of this study was to examine the effect of compensation on employee performance, the effect of compensation on job satisfaction, the effect of job satisfaction on employee performance, the effect of job placement on job satisfaction, at RSUD dr. Dradjat Prawiranegara. The population in this study were nurses with non-civil servant status or nurses with voluntary labor status (TKS) who were still working at RSUD dr. Dradjat Prawiranegara. The number of samples is determined based on the number of indicators of the 4 variables used multiplied by 5, the total of all indicators is 20 x 5, total of Sample is 100 respondents, the sampling method uses the Non Random Sampling technique, because the population and sample have been determined, namely Non-PNS Nurses.The results of this study indicate that there is a significant effect of compensation on employee performance, there is a significant effect of compensation on job satisfaction, there is a significant effect of job satisfaction on employee performance, there is a significant effect of job placement on job satisfaction, and there is a significant effect of job placement on employee performance.